(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article highlights the current importance of the analysis of the experience of foreign countries in the investigation of crimes in the field of ecology. In the investigation of crimes in the field of ecology, international documents and norms of our national legislation are interpreted. The author analyzed the existing problems and shortcomings in the investigation of crimes in the field of ecology.